Social semiotics of news reports on the change of the halal logo in detik.com for March 2022 - Khotimah, Nurul; Mastika, Silma Ulqiatul (Islamic Communication Journal, 2023)
The news reports on the change of the halal logo issued by the Halal Product Assurance Organizing Agency (BPJPH) officially replaced the current halal logo from the Indonesian Ulema Council (MUI), followed by its authority, based on Law Number 33/2014 on Halal Product Assurance. The halal logo is not only an accessory of the label but also the leading indicator to identify and guarantee the halalness of a product. This paper aims to show the social semiotics of news reports by examining issues on the new halal logo on Detik.com for March 2022. The research data was collected from the online news portal Detik.com and other articles and supporting journals. Based on this problem, this study used a descriptive qualitative method using the social semiotic analysis approach by M.A.K Halliday. The result showed that Detik.com delivered various news reports; some favored the new halal label, while other reports were neutral and even harmful. The implications of this research suggest that our perspective on the news discerns more from the text and its context. ***Pemberitaan perubahan logo halal yang dikeluarkan Badan Penyelenggara Jaminan Produk Halal (BPJPH) resmi menggantikan logo halal yang ada saat ini dari Majelis Ulama Indonesia (MUI), berikut kewenangannya berdasarkan Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal. Logo halal tidak hanya menjadi pelengkap label tetapi juga menjadi indikator utama untuk mengidentifikasi dan menjamin kehalalan suatu produk. Tulisan ini bertujuan untuk mengkaji semiotika sosial terkait pemberitaan isu logo halal baru di Detik.com bulan Maret 2022. Data penelitian dikumpulkan dari portal berita online Detik.com dan artikel serta jurnal pendukung lainnya. Berdasarkan permasalahan tersebut, penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan analisis semiotika sosial oleh M.A.K Halliday. Hasilnya menunjukkan bahwa Detik.com menyampaikan pemberitaan yang beragam; beberapa mendukung label halal baru, sementara laporan lainnya netral dan bahkan negatif. Implikasi dari penelitian ini menunjukkan bahwa perspektif kita terhadap berita lebih memahami teks dan konteksnya.